The role of relationship value in manufacturer-retailer context - Prasetya, Prita; Najib, Mukhamad; Soehadi, Agus W. (Penerbit Universiti Kebangsaan Malaysia, 2021)
The content and form of relationship value dominate the literature. The study aims to add to relationship value research by examining its dimensions and outcomes. The relationship value presents a new taxonomy beyond the cost and benefit conception of value that dominates existing literature. Its consisting of four dimensions, i.e., personal, financial, knowledge and strategic value. The focus of the research, which synthesizes a conceptual framework from the relationship value framework, is on business-to-business situations and the value of the relationship to the manufacturer. Using structural equation modeling, the study examines the influence of relationship value on relational trust, relational commitment and performance. The sample covers 259 retailers categorized as Small and Medium Enterprises (SMEs) in Indonesia. It was found that relationship value drives relational trust and relational commitment perceived by retailers. In addition, both of them are key factors that nurture the value of relationships between manufacturers and retailers. Finally, relationship value is a determinant of business performance.